2016
DOI: 10.3390/su8090928
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Time-Weighted Dynamic Energy Efficiency, Energy Decoupling Rate, and Decarbonization: An Empirical Study on G7 and BRICS

Abstract: Abstract:Energy is a critical factor of economic growth, but the overuse of it results in global warming and climate change. Hence, energy efficiency improvement can help mitigate climate change and prevent economic losses or even ecological extinction. The data envelopment analysis (DEA) approach has been extensively applied for energy efficiency estimation, but past studies of this estimation employ a static mode that does not consider consecutive periods and the carry-over effect. This study estimates energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…These results are consistent with the findings of Tu et al (2016) who found that Brazil, Russia, India, China, and South Africa had lower achievement standard ratios of the energy decoupling rate. It therefore seems clear that even non-members of ASEAN, particularly those experiencing relatively rapid economic growth, need to pay more attention to improving their energy usage.…”
Section: Results Of the Energy Decoupling Ratesupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the findings of Tu et al (2016) who found that Brazil, Russia, India, China, and South Africa had lower achievement standard ratios of the energy decoupling rate. It therefore seems clear that even non-members of ASEAN, particularly those experiencing relatively rapid economic growth, need to pay more attention to improving their energy usage.…”
Section: Results Of the Energy Decoupling Ratesupporting
confidence: 92%
“…Third, from the Clean Development Mechanism (CDM), which is defined in Article 10 of the Kyoto Protocol, Tu et al (2016) indicated that the environmental and energy technologies of developed countries should be made readily transferrable to developing countries. Therefore, we suggest that ASEAN+6 should adopt advanced technology/equipment from developed countries in order to reduce their production costs, which will indirectly increase their wealth and lead to further improvements in environmental quality.…”
Section: Policy Implications For Asean+6mentioning
confidence: 99%
“…Csereklyei et al [33] proposed the factors driving global energy use growth are economic growth, energy intensity, and weak decoupling. Tu et al [34] conducted an empirical study of the Group of Seven (G7) and BRICS countries to analyze energy decoupling rates and decarbonization trends to improve energy efficiency and mitigate global warming and climate change. Schandl et al [35] used a new approach to economic and environmental models to assess the decoupling potential of 13 world regions and global regions.…”
Section: Research At the Global Or Multiple National Levelmentioning
confidence: 99%
“…In 1987, system of innovation was first used in the Freeman's book on "technology policy and economic performance in Japan" in the form of publication (Freeman, C., 1987). The current literature on the national innovation systems (NIS) of developing economies such as Brazil, Russia, India, China and South Africa (BRICS),was bound to four kinds of research: (1) theoretical and historical research of the national innovation systems of the BRICS (Cassiolato & Vitorino, 2009;Sceri et al, 2010;Zaichenko, 2014), (2) examining the causality between national innovation systems (NIS) variables and their effect on economic growth or development (Alnafrah & Bogdanova, 2018;Rao Nicholson et al, 2017), (3) practicing machine learning technology to assess the structural durability and flaws of national innovation systems (NIS) (Alnafrah, 2019;Alnafrah & Zeno, 2019), and (4) evaluating the performance of particular innovative industries or subsystems for example energy, insurance industry and ICT industry (Song et al, 2013;Tu et al, 2016;Huang & Eling, 2013;Biryukova & Matiukhina, 2019). Productivity growth path of national innovation system (NIS) and its linkage with technological progress in the process of catch-up (Zabala Iturriagagoitia et al, 2020) Innovation system has evolved broadly recognized in to two reasons in innovation research studies, First, in view of the fact that, it departs away from the predictable linear approached and second, research & development to describe the transformations during innovation among the countries (Radosevic, 1998).…”
Section: Introductionmentioning
confidence: 99%